SHUKRA; THE ESSENCE OF ALL OTHER DHATU: A REVIEW - Kiran Bhikaji, Pawar; Sudhakar, Meshram Dnyaneshwar; Manju Namdev, Jadhav; Sahebrao, Dhimdhime Ravindra; Pundlikrao, Borse Vilas (International Journal of Ayurveda and Pharma Research, 2015)
Human body is made up of seven Dhatus (seven categories of tissues). Shukradhatu is located in entire body. Shukra is white, pure, excellent Dhatu, which is considered as best among all seven Dhatus. Shukra is word originated from Shucha Dhatu which means pure or excellent. Teja, Reta, Bijam, Virayam, Indriyam are some of the synonyms of Shukradhatu. Shukra means bright, pure and radiant. Shukra is the seventh and final Dhatu in the Dhatus formation cycle. In metabolism of Shukradhatu nutrients essential for Shukradhatu are digested by Shukuradhatwagni and forms Shukradhatu. For the formation of Shukradhatu one month period is essential. Individuals having the excellence of Shukradhatu are shown physical & psychological characteristics. According to texts of Ayurveda, Shukradhatu is pervading all over the body. It gives courage to a person. It creates softness in the mind. It is responsible for strength of individuals. Vitiation of Shukradhatu shows Shukradhatu dusti (pathology) in the form of Vriddhi (hyper state) or Kshaya (waning). This vitiation may leads to mainly infertility and many other physical as well as psychological disorders. Therefore, it has a vital role in context to reproduction as well as to maintain physical and mental health. It is present in our body in invisible form like Ghee in the milk. It is the end product of Dhatu parinaama or formation of Dhatus. So it is considered as an essence of all Dhatus. As it is essence of all other Dhatus, Charak samhita and Sushrut samhita has not described its Mala (waste).